Hubungan kuantitatif struktur-kinetika distribusi senyawa sulfonamida = Quantitative Structure-Distribution Kinetics Relationship of Sulfonamide Compounds - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Quantitative Structure-Pharmacokinetics Relationship (QSPR) has given a logical baseline to attain more rational drugs design, therefore it holds an important position in new drug development. The present research is aimed to study Quantitative Structure-Distribution kinetics Relationship of sulfonamide compounds and to develop an HPLC method for lipophilicity measurement of the sulfonamides. The study was applied to define the physico-chemical parameters (log Kw and pKa) and distribution kinetics parameter (Vd^). Apartition coefficient Log Kw as a parameter for lipophilicity was obtained by HPLC (stationary phase = ODS C18, mobile phase = methanol: acetate buffer pH 4 with various concentrations of methanol of 70, 80, and 90%). To determine the distribution parameter values for the seven sulfonamides, a completely randomized design was adopted, and a single intravenous dose of 40 mg/kg body weight of male Wistar rats. The blood concentrations of each sulfonamide were assayed using a modified Bratton-Marshall method. Parameter values were obtained from a non-compartmental method by CPL2 software. Regression analysis was performed using the Microstat software to search for correlation between dependent (Vd^) and independent variables (Log Kw, pKa). The comparison of Log Kw with Log P (computed by Hansch method through C log P program) showed a good correlation, which means that the HPLC method (stationary phase =ODS C18, mobile phase = methanol:acetate buffer pH 4) could be used as an alternative method to define the sulfonamide lipophilicity. The equations which described adequately the correlation of both variables is 1000/VdB = - 3.75 Log Kw + 11.53 pKa - 0.748 pKa2- 33.9 (n=7